Saint-Simons vision av ett enat Europa (Sociologisk Forskning, 1994)
Saint-Simon's vision of a united EuropeWhile there exists a considerable literature on Saint-Simon’s work as a whole, practically no research has been devoted to the theme of a united Europe in his writings. This essay traces this theme from his first to his last writings. While in the beginning of his career Saint-Simon emphasized that science would save Europe from its crisis and also unite it, he later emphasized the role of industry. In his famous pamphlet from 1814, De la réorganisationde la société européenne, Saint-Simon also suggested what the political structure of a united Europe may look like. What is remarkable about Saint-Simon’s mature vision of a united Europe is that Saint-Simon here brings together three separate ideas from the18th and 19th century: (1) Europe has to be reorganized if there is to be an end to all the wars; (2) Europe must get a government that is independent of the individual countries; and (3) industry will bind people together and play a key role in Europe’s unification. An effort is made - through Durkheim’s theory of collective representations - to explore the roots of Saint-Simon’s vision in the French Revolution and its aftermath. Paralells between Saint-Simon’s ideas and those of Jean Monnet are discussed in the last part of the article.